The significance of health opinion for planning health education - Górajek-Jóźwik, Jolanta; Borek, Elżbieta; Ciechaniewicz, Wiesława; Żurawska vel Dziurawiec, Kinga (Polish Journal of Public Health, 2009)
Introduction. The growing interest in the health issues in its biological, psychological, social and spiritual dimension is refl ected in the attempts of multidisciplinary approach towards this subject.Aim. The study aims to answer the questions: How do the respondents evaluate their current state of health? How do they define the term “health” in its four aspects: physical, psychological, social and spiritual? Does the evaluation of the health condition give the basis for planning the health education?Material and methods. Diagnostic survey (tool: non-standard questionnaire). The examined group: 119 adults. Results. The respondents find no diff culties in defining the physical health but when describing the sanity, they disregard the emotional sphere when evaluating the social health - they mostly focus on the functioning of the society and when expressing the spiritual health they concentrate on the conscience and belief in God.Conclusions. Adult person knows what health means, particularly in its physical dimension. There are great problems with describing the essence of social and spiritual health. The illustrated diagnosis of the health condition lists the areas which should constitute the subject of theoretical and practical interest of health educators.